IMPLEMENTASI E-PROBLEM BASED LEARNING (E-PBL) AKUNTANSI MANAJEMEN PADA MAHASISWA STIE ASIA MALANG - Murniati, Aniek; Hermawan, Aditya (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2018)
This study is a descriptive study on the implementation of E-problem based learning (EPBL) Management accounting. The research data is based on observation ofthe application of learning method. Observation is done by interviewing and observingstudents who are implementing e-PBL in management accounting courses. Observations and interviews on lecturers who implement this learning model. Theresults explained that E-PBL facilitate students and lecturers to deliver learningmaterials and evaluate or utilize facilities provided by departments / agencies. E-PBL is alearning will help lecturers to facilitate the delivery of learning materials for easy tounderstand students. E-PBL in Evaluation / assessment of learning as one way to determine the ability ofstudents in following the learning will be very easy. With e-PBL, every studentautomatically has to be absent online. to the task also can directly check online.Communication and inertaksi among lecturers, students will be easier.